Phenols, Tannins, and Total Colonies of Phenol-Degrading Bacteria in the Natural and Cultivated Peatlands - Wandanil Wandanil; Evi Gusmayanti; Gusti Zakaria Anshari (Jurnal Ilmu Pertanian Indonesia, 2025)
Phenols play an important role in inhibiting the decomposition rate of peats. This research compares the total phenols, tannins, and colonies of phenol-degrading bacteria in natural and cultivated peatlands. The work was conducted from September to December 2023 on the peatlands in Pontianak, West Kalimantan. Samples of 60 cm3 were collected from the peat surface. The samples were taken from 4 types of peats, namely natural peats covered by ferns (A), cultivated peat with raised beds (B), cultivated peat with raised beds ameliorated with lime and beef manure (C), and cultivated peat with raised beds ameliorated with lime, beef manure, and Jadam fertilizer (D). The total phenols content was measured using the Folin-Ciocalteu 10% method using a UV-Vis spectrophotometer at a wavelength of 765 nm. The total tannins content was measured using the Folin-Denis method using a UV-Vis spectrophotometer at a wavelength of 740 nm. Total bacterial colonies were counted using the Total Plate Count method on selective Mineral Salt Medium (MSM) agar with the addition of phenol solution. The results showed that the average total phenols and tannins content values were generally low in the cultivated peats, particularly in the raised bed (B). The results indicate that the cultivated peat accelerates the activity of phenol-degrading bacteria. Keywords: Jadam fertilizer, phenols, phenol-degrading bacteria, peats, tannin